A potential role for guanine nucleotide-binding protein in the regulation of endosomal proton transport. - Gurich, R W (1991)
The effects of guanosine 5'-triphosphate (GTP) and GTP-gamma-S, known activators of GTP binding proteins, on proton transport were investigated in endosome-enriched vesicles (endosomes). Endosomes were prepared from rabbit renal cortex following the intravenous injection of FITC-dextran. The rate of intravesicular acidification was determined by measuring changes in fluorescence of FITC-dextran. Both GTP and GTP-gamma-S stimulated significantly the initial rate of proton transport. In contrast, GDP-beta-S, which does not activate GTP binding proteins, inhibited proton transport. The rank order of stimulation was GTP-gamma-S greater than GTP greater than control greater than GDP-beta-S. GTP-gamma-S stimulation of proton transport was also observed under conditions in which chloride entry was eliminated, i.e., 0 mM external chloride concentration in the presence of potassium/valinomycin voltage clamping. GTP-gamma-S did not affect proton leak in endosomes as determined by collapse of H+ ATPase-generated pH gradients. ADP ribosylation by treatment of endosomal membranes with pertussis toxin revealed two substrates corresponding to the 39-41 kD region and comigrating with alpha i subunits. Pretreatment of the membranes with pertussis toxin had no effect on proton transport in the absence of GTP or GTP-gamma-S. However, pretreatment with pertussis toxin blocked the stimulation of proton transport by GTP. In contrast, as reported in other membranes by others previously, pertussis toxin did not prevent the stimulation of proton transport by GTP-gamma-S. These findings, taken together, indicate that GTP binding proteins are present in endosomal membranes derived from renal cortex and that activation of G protein by GTP and GTP-gamma-S stimulates proton transport in a rank order identical to that reported for other transport pathways modulated by Gi proteins. Therefore, these studies suggest that G proteins are capable of stimulating the vacuolar H ATPase of endosomes directly.